EXAFS analysis of cadmium(II) adsorption to kaolinite - Vasconcelos, Igor Frota de (2008)
The local molecular structure of Cd sorbed to kaolinite was examined with X-ray absorption fine structure spectroscopy (XAFS) over a range of pH and initial Cd solution concentrations, ([Cdaq]in). Quantitative analysis of kaolinite samples with [Cdaq]in of 100 μM and pH 7, shows a single hydration sphere around Cd, consistent with an outer-sphere adsorption complex. At pH 9, a Cd–M coordination (where M stands for Si or Al) at second shell distance indicates the formation of inner-sphere adsorption complex(es) on edge sites. Although adsorption to Al edge sites is probably preferred, the similarity in atomic numbers between Al and Si and the small difference in bond lengths prevents us from distinguishing complexation to Si- versus Al-edge sites based on the XAFS data. The possibility of precipitation of Cd solid phases was ruled out due to similar local environment around Cd in samples prepared under air (where carbonate species would be present) and N2 atmospheres, and the absence of a Cd–Cd coordination characterizing a Cd-bearing solid phase. Finally, analysis of kaolinite samples with [Cdaq]in of 3 μM, 10 μM, and 100 μM at pH 9 shows a consistent change in Cd–M distance and Debye–Waller factor as a function of [Cdaq]in, suggesting a change in the type of inner-sphere complex being formed as a function of loading. Whether this means that there is a change in the relative importance of Al versus Si edge sites with loading, or whether adsorption of Cd to edge sites alters binding to other nearby sites, or some other factor, has not been determined at this time.